The Role of Premotor Areas in Dual Tasking in Healthy Controls and Persons With Multiple Sclerosis: An fNIRS Imaging Study - Saleh, Soha; Sandroff, Brian M.; Vitiello, Tyler; Owoeye, Oyindamola; Hoxha, Armand; Hake, Patrick; Goverover, Yael; Wylie, Glenn; Yue, Guang; DeLuca, John (Frontiers in Behavioral Neuroscience, 2018)
Persons with multiple sclerosis (pwMS) experience declines in physical and cognitive abilities and are challenged by dual-tasks. Dual-tasking causes a drop in performance, or what is known as dual-task cost (DTC). This study examined DTC of walking speed (WS) and cognitive performance (CP) in pwMS and healthy controls (HCs) and the effect of dual-tasking on cortical activation of bilateral premotor cortices (PMC) and bilateral supplementary motor area (SMA). Fourteen pwMS and fourteen HCs performed three experimental tasks: 1) single cognitive task while standing (SingCog), 2) single walking task (SingWalk), and 3) dual-task (DualT) that included concurrent performance of the SingCog and SingWalk. Six trials were collected for each condition and included measures of cortical activation, WS, and CP. WS of pwMS was significantly lower than HC, but neuropsychological (NP) measures were not significantly different. PwMS and HC groups had similar DTC of WS, while DTC of CP was only significant in the MS group; processing speed and visual memory predicted 55% of this DTC. DualT versus SingWalk recruited more right-PMC activation only in HCs and was associated with better processing speed. DualT versus SingCog recruited more right-PMC activation and bilateral-SMA activation in both HC and pwMS. Lower baseline walking speed and worse processing speed measures in pwMS predicted higher recruitment of right-SMA activation suggesting maladaptive recruitment. Lack of significant difference in NP measures between groups does not rule out the influence of cognitive factors on dual-tasking performance and cortical activations in pwMS, which might have a negative impact on quality of life.